ICSI from the beginning to where we are today: are we abusing ICSI?. Issue 3 (2019) - Keating, Derek; Cheung, Stephanie; Parrella, Alessandra; Xie, Philip; Rosenwaks, Zev; Palermo, Gianpiero D.
Abstract : Intracytoplasmic sperm injection (ICSI) was first described in 1992 providing couples, struggling with male factor infertility resulting in complete and unexpected fertilization failure with standard in vitro insemination, the chance to conceive a child of their own. In the 2 and a half decades since, ICSI has gained popularity worldwide and has become the most utilized insemination method at our center due to its versatility and abundance of indications. In this brief report, we examine the achievements and accomplishments of ICSI while we also question whether ICSI may be suffering abuse from overuse.